Color Doppler ultrasound in high-low risk pregnancies and its relationship to fetal outcomes: a cross-sectional study - Dixit, Snehil; Dixit, Nitin Arun; Rawat, Anil; Bajpai, Akanksha; Alelyani, Magbool; Sabah, Zia Ul; Raghuwanshi, Shailendra (Frontiers in Pediatrics, 2024)
Objective: To calculate the multivessel color Doppler indices in high-risk and low-risk pregnancies and relate these to fetal outcomes. Methods: The investigation involved 60 patients who were pregnant. The patients were separated into groups according to assessment of low and high risk. The patients underwent color Doppler ultrasonography to detect the maternal and fetal blood vessels, and the measured Doppler indices were then analyzed for any association with fetal outcomes. Results: The gestational stages (in weeks) of the participants at the respective times of investigation and delivery were 32.06 ± 2.98 and 36.2 ± 1.78 in the low-risk group and 29.21 ± 1.95 and 29.83 ± 1.86 in the high-risk group. The pulsatility index (PI), resistive index (RI), and systolic/diastolic ratio (SD) decreased with gestation length in the low-risk group, whereas in the high-risk group, these values increased in the uterine and umbilical arteries. With increased gestational stage, MCA-PSV (peak systolic velocity) in the middle cerebral artery (MCA) increased, while PI decreased. Pulsatile and reversal flow of the uterine vein, the vein of Galen, and the umbilical vein were noted in high-risk pregnancies, and these negatively affected the fetal outcome. The fetal venous parameters were more specific and sensitive for predicting an unfavorable fetal outcome than the arterial factors, with a greater negative predictive value.The results of our study indicate that abnormal Doppler indices of the blood vessels in high-risk pregnant patients will result in adverse clinical outcomes. Therefore, the patients can be monitored and managed accordingly using Doppler ultrasonography.